Fabrication, Characterization, and Biological Activity of Avermectin Nano-delivery Systems with Different Particle Sizes - Anqi Wang; Yan Wang; Changjiao Sun; Chunxin Wang; Bo Cui; Xiang Zhao; Zhanghua Zeng; Junwei Yao; Dongsheng Yang; Guoqiang Liu; Haixin Cui (Nanoscale Research Letters, 2018)
Abstract Nano-delivery systems for the active ingredients of pesticides can improve the utilization rates of pesticides and prolong their control effects. This is due to the nanocarrier envelope and controlled release function. However, particles containing active ingredients in controlled release pesticide formulations are generally large and have wide size distributions. There have been limited studies about the effect of particle size on the controlled release properties and biological activities of pesticide delivery systems. In the current study, avermectin (Av) nano-delivery systems were constructed with different particle sizes and their performances were evaluated. The Av release rate in the nano-delivery system could be effectively controlled by changing the particle size. The biological activity increased with decreasing particle size. These results suggest that Av nano-delivery systems can significantly improve the controllable release, photostability, and biological activity, which will improve efficiency and reduce pesticide residues.